PENDEKATAN SUFISTIK DALAM PENDIDIKAN ISLAM BERWAWASAN PERDAMAIAN - Gani, A (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract Conflict becomes part of contemporary phenomena that embraces all dimensions of human life, starting from the level of individuals, society, to relations between countries. Conflict in all of its variety, both economic, political conflicts, even conflicts between civilizations, cannot be separated from the